Determinants of Farmers' Interest in Cultivating Herbal Crops in the Special Region of Yogyakarta: a Study on Motivational and Economic Influences - Hanif, Muhammad Farhan; Prayoga, Kadhung; Handayani, Migie (Jurnal AGRISEP, 2024)
Herbal plants are horticultural commodities rich in health benefits. In DI Yogyakarta, these plants are frequently used to make traditional herbal medicine (jamu), serving as natural remedies for the community. Despite having significant land amounts and relatively good production levels, the overall yield of DI Yogyakarta's herbal plants remain suboptimal. This is attributed to the low number of farmers and their low time allocation for cultivation, which stemmed from decreasing interest among farmers in herbal plant cultivation, influenced by time constraints and economic challenges. Identifying factors that could increase farmers' interest in herbal plant cultivation is essential to enhance interest. This study aims to analyze how motivation, needs, family support, availability of facilities, ease of cultivation, production capacity, and quality, price stability, and income influence farmers' interest in cultivating herbal plants in DI Yogyakarta. The research was conducted from April 2024 to May 2024. This research used a quantitative survey method. The samples were 20 farmers (KT Lombok Ijo), 15 farmers (KWT Sekar Kenanga), and 22 farmers (KWT Sumber Rejeki). Data analysis employed descriptive analysis and multiple linear regression. Results showed that needs and price stability affected farmers' interest in cultivating herbal plants in DI Yogyakarta, indicating that the fulfillment of primary needs and price stability during weather changes proven to affect farmers' interest in cultivating herbal plants. DI Yogyakarta's government should boost farmers’ interest by aligning it with the actual conditions faced by farmers.